Acute Effects of Sildenafil and Dobutamine in the Hypertrophic and Failing Right Heart in Vivo. (1st September 2013) - Andersen, Asger; Nielsen, Jan M.; Rasalingam, Sivagowry; Sloth, Erik; Nielsen‐Kudsk, Jens Erik
Abstract : The purpose of this study was to investigate whether acute intravenous administration of the phosphodiesterase type 5 (PDE‐5) inhibitor sildenafil in a single clinically relevant dose improves the in vivo function of the hypertrophic and failing right ventricle (RV). Wistar rats ( n = 24) were subjected to pulmonary trunk banding (PTB) causing RV hypertrophy and failure. Four weeks after surgery, they were randomized to receive an intravenous bolus dose of sildenafil (1 mg/kg; n = 7), vehicle ( n = 6), or dobutamine (10 μg/kg; n = 6). Invasive RV pressures were recorded continuously, and transthoracic echocardiography was performed 1, 5, 15, 25, 35, 50, 70, and 90 minutes after injecting the bolus. Cardiac function was compared to baseline measurements to evaluate the in vivo effects of each specific treatment. The PTB procedure caused significant hypertrophy, cardiac fibrosis, and reduction in RV function evaluated by echocardiography (TAPSE) and invasive pressure measurements. Sildenafil did not improve the function of the hypertrophic failing right heart in vivo, measured by TAPSE, RV systolic pressure (RVsP), and dp/dt max . Dobutamine improved RV function 1 minute after injection measured by TAPSE (0.1242 ± 0.03 vs. 0.1565 ± 0.04 cm; P < 0.001), RVsP (83 ± 11 vs. 107 ± 11 mmHg; P < 0.001), and dp/dt max (3, 136 ± 521 vs. 4, 489 ± 706 mmHg/s; P < 0.001). Acute administration of the PDE‐5 inhibitor sildenafil in a single clinically relevant dose did not modulate the in vivo function of the hypertrophic failing right heart of the rat measured by echocardiography and invasive hemodynamics. In the same model, dobutamine acutely improved RV function.